Fall detection system for elderly people : a neural network approach - Igrejas, Getúlio (2014)
In this work a new approach for a fall detection system is proposed. The device integrates a 3-axis accelerometer and a 3-axis gyroscope to measure linear acceleration and angular velocities, respectively. Information from both sensors is used to characterize movements through selected features extracted from raw data. A classification system based on a Feedforward Backpropagation Neural Network is then trained, based on the extracted features. The performed tests present low false positives and low false negatives rates with good specificity and sensitivity values.